“We are the sun for our community:” Partnering with community health workers/promotores to adapt, deliver and evaluate a home-based collaborative care model to improve equity in access to quality depression care for older U.S. Latino adults who are underserved - Steinman, Lesley E.; Gasca, Amelia; Hoeft, Theresa J.; Raue, Patrick J.; Henderson, Stuart; Perez, Rosa; Huerta, Alfredo; Fajardo, Alex; Vredevoogd, Melinda A.; James, Katherine; Hinton, Ladson; Rath, Laura; et al. (Frontiers in Public Health, 2023)
Background While depression is a leading cause of poor health, less than half of older adults receive adequate care. Inequities in both access and outcomes are even more pronounced for socially disadvantaged older adults. The collaborative care model (CCM) has potential to reduce this burden through community-based organizations (CBOs) who serve these populations. However, CCM has been understudied in diverse cultural and resource-constrained contexts. We evaluated the implementation and effectiveness of PEARLS, a home-based CCM adapted with and for community health workers/promotores (CHWs/Ps). Methods We used an instrumental case study design. Our case definition is a community-academic partnership to build CHW/P capacity for evidence-based depression care for older U.S. Latino adults in the Inland Empire region of California (2017–2020). We aimed to understand adaptations to fit local context; acceptability, feasibility, and fidelity; clinical effectiveness; and contextual determinants of implementation success or failure. Data sources included quantitative and qualitative administrative and evaluation data from participants and providers. We used descriptive statistics and paired t-tests to characterize care delivery and evaluate effectiveness post-intervention, and deductive thematic analysis to answer other aims. Findings This case study included 152 PEARLS participants and nine data sources (N = 67 documents). The CBO including their CHWs/Ps partnered with the external implementation team made adaptations to PEARLS content, context, and implementation strategies to support CHWs/Ps and older adults. PEARLS was acceptable, feasible and delivered with fidelity. Participants showed significant reductions in depression severity at 5 months (98% clinical response rate [mean (SD), 13.7 (3.9) drop in pre/post PHQ-9; p < 0.001] and received support for 2.6 social needs on average. PEARLS delivery was facilitated by its relative advantage, adaptability, and trialability; the team's collective efficacy, buy-in, alignment with organization mission, and ongoing reflection and evaluation during implementation. Delivery was challenged by weak partnerships with clinics for participant referral, engagement, reimbursement, and sustainability post-grant funding. Discussion This case study used existing data to learn how home-based CCM was adapted by and for CHWs/Ps to reduce health inequities in late-life depression and depression care among older Latino immigrants. The CBOs and CHWs/Ps strong trust and rapport, addressing social and health needs alongside depression care, and regular internal and external coaching and consultation, appeared to drive successful implementation and effectiveness.